2012
DOI: 10.2527/jas.2011-4454
|View full text |Cite
|
Sign up to set email alerts
|

Valine and isoleucine requirement of 20- to 45-kilogram pigs1,2

Abstract: Three experiments were conducted to determine the Val and Ile requirements in low-CP, corn-soybean meal (C-SBM) AA-supplemented diets for 20- to 45-kg pigs. All experiments were conducted for 26 to 27 d with purebred or crossbred barrows and gilts, which were blocked by initial BW. Treatments were replicated with 5 or 6 pens of 3 or 4 pigs per pen. At the beginning of Exp. 1 and the end of all experiments, blood samples were obtained from all pigs to determine plasma urea N (PUN) concentrations. All diets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
4
18
1
1
Order By: Relevance
“…There are not many experiments reporting the optimum SID Val : Lys ratio for the maximum growth performance of piglets. However, recent investigations indicate that the optimum SID Val : Lys ratio for piglets is ranging from 0.63 to 0.70 (Gaines et al, 2011;Gloaguen et al, 2011;Waguespack et al, 2012). The results of the present study showed that the maximum ADFI, ADG and G : .…”
contrasting
confidence: 41%
“…There are not many experiments reporting the optimum SID Val : Lys ratio for the maximum growth performance of piglets. However, recent investigations indicate that the optimum SID Val : Lys ratio for piglets is ranging from 0.63 to 0.70 (Gaines et al, 2011;Gloaguen et al, 2011;Waguespack et al, 2012). The results of the present study showed that the maximum ADFI, ADG and G : .…”
contrasting
confidence: 41%
“…Gaines et al (2011) concluded that the SID Val:Lys ratio for 21.4-to 32.6-kg growing pigs was approximately 0.65 based on a linear broken-line model and using growth performance as the response criteria. Waguespack et al (2012) demonstrated that for 20-to 45kg pigs, the SID Val:Lys ratio was about 0.67 to 0.70. In the present experiment, the dietary SID Val:Lys ratios required for 26-to 46-, 49-to 70-, 71-to 92-, and 94-to 119kg pigs were 0.62, 0.66, 0.67, and 0.68, respectively, using a linear broken-line model, which are similar to the NRC (2012) recommendations of 0.65, 0.65, 0.66, and 0.67 for 25-to 50-, 50-to 75-, 75-to 100-, and 100-to 130-kg pigs, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Much of the literature on the Val requirement summarized by NRC (2012) focused on weaned piglets. However, research on the requirements for Val for growing and finishing pigs is scarce and the results vary among the different studies (Lewis and Nishimura, 1995;Gaines et al, 2011;Waguespack et al, 2012). Therefore, the aim of this study was to evaluate the SID Val:Lys ratio required for growing and finishing pigs fed low CP diets supplemented with crystalline AA.…”
Section: Introductionmentioning
confidence: 99%
“…A 10% reduction in the isoleucine concentration (below the requirement) resulted in a 15% reduction in feed intake and a 21% reduction in daily gain (Van Milgen et al, 2012). Waguespack et al (2012) investigated the SID isoleucine to lysine ratio in 20-45 kg pigs, fed low crude protein diets supplemented with crystalline AA ad libitum. They used corn-soybean meal diets without blood products.…”
Section: Isoleucinementioning
confidence: 99%